Immunomagnetic separation combined with RT-qPCR for evaluating the effect of disinfectant treatments against norovirus on food contact surfaces. (November 2018) - Lee, Hee-Min; Yang, Ji-Su; Yoon, So-Ra; Lee, Jae Yong; Kim, Su-Ji; Lee, Hae-Won; Kim, Sung Hyun; Ha, Ji-Hyoung
Abstract: Despite the importance of preventing the spread of human norovirus (NoV), effective disinfectants are lacking. In this study, the efficacy of disinfectants against NoV on various non-porous surfaces was investigated by immunomagnetic separation (IMS) and quantitative real-time reverse transcription (RT-q)PCR. Monoclonal anti-NoV antibody-conjugated magnetic beads captured intact viral particles for RT-qPCR after the treatment of surfaces with disinfectants. Viral suspensions of approximately 5.97 log10 genomic copies were inoculated onto rubber, glass, stainless steel, ceramic tile, wood, and polyvinyl chloride surfaces. Various elution buffers were used to elute NoV from surfaces. Ethanol (50–70%), sodium hypochlorite (NaOCl, 100–1000 ppm), sodium metasilicate (SMS, 0.1% and 0.3%), and quaternary compounds (1000–2000 ppm) were investigated as disinfectants; the observed reductions were <1 log10, except for SMS (1.17 ± 0.21 to 2.71 ± 0.06 log10 reduction) and 700–1000 ppm NaOCl (1.04 ± 0.07 to 2.03 ± 0.05 log10 reduction). Ethanol and quaternary compounds exhibited low efficacy against NoV GII.4 on all surfaces. These results indicated that SMS is the most effective disinfectant and emphasized the need to develop suitable agents to inactivate NoV on surfaces. Highlights: Chemical disinfectants against NoV were analyzed on non-porous surfaces. Sodium metasilicate (0.3%) had the highest efficacy against NoV on all surfaces. Ethanol and quaternary compounds were not effective against NoV GII.4. SMS is a suitable disinfectant to reduce NoV GII.4 in the food industry.